The value of bioimpedance analysis in the assessment of hydration and nutritional status in children on chronic peritoneal dialysis - Wei Yuan; Minghui Yu; Zhiqing Zhang; Qianfan Miao; Jiaojiao Liu; Hui Zhang; Qing Zhou; Jing Chen; Yihui Zhai; Xiaoyan Fang; Hong Xu; Qian Shen (Renal Failure, 2024)
Bioimpedance analysis (BIA)–body composition monitoring (BCM) has been used to evaluate the hydration and nutritional status of adults and children on dialysis. However, its clinical application still has challenges, so further exploration is valuable. We used BIA-BCM to evaluate the hydration and nutritional status of children undergoing chronic peritoneal dialysis from 1 July 2021 to 31 December 2022 in the Children’s Hospital of Fudan University to explore the clinical value of this method. A total of 84 children on chronic peritoneal dialysis (PD) were included. In the PD group, 16 (19.05%) and 31 (36.90%) had mild and severe overhydration (OH), respectively; 41.27% (26/63) had a low lean tissue index (LTI). In the PD group, patients with relative OH (Re-OH) > 5.6% had significantly higher systolic blood pressure (SBP) and SBP z score (SBPz). Patients with LTI > 12% had significantly higher body mass index (BMI) and BMI z score (BMIz). Canonical correlation analysis indicated a linear relationship (ρ = 0.708) between BIA-BCM hydration and the clinical hydration indicator and a linear relationship (ρ = 0.995) between the BIA-BCM nutritional indicator and the clinical nutritional indicator. A total of 56% of children on chronic peritoneal dialysis had OH, and 41% had a low LTI. In PD patients, SBP and SBPz were correlated with BIA-BCM Re-OH, and BMI and BMIz were correlated with BIA-BCM LTI. BIA-BCM indicators have good clinical value in evaluating hydration and nutrition.